TWO-MICA GRANITES IN THE NEOSOME OF THE RIKOLATVI AGMATITE STRUCTURE - Shcherbakova T.F. (My University, 2001)
The two-mica granites in the neosomes of a large agmatite structure were determined to be heterogeneous. They differ in major- and trace-element composition, age, and origin. The rocks are geochemically classified into Rb-rich granites and granites with high concentrations of Rb, Sr, and Ba but very low Zr and REE. The genesis of the neosome granite was caused by changes in the P-T conditions and fluid regime in response to multistage intense deformation occurring, perhaps, as a consequence of collision between the Kola and Karelian plates.